Assessment of knowledge, attitudes and practices towards newborn screening for congenital hypothyroidism before and after a health education intervention in pregnant women in a hospital setting in Pakistan. Issue 2 (8th March 2018) - Tariq, Batha; Ahmed, Ayesha; Habib, Atif; Turab, Ali; Ali, Noshad; Soofi, Sajid Bashir; Nooruddin, Shanila; Kumar, Rekha J; Tariq, Amin; Shaheen, Fariha; Ariff, Shabina
Abstract: Background: Most congenital hypothyroidism (CH) is not avertable; however, the adverse effects of CH are preventable with early detection and treatment. It is a common congenital endocrine disorder that affects 1 in 2000–4000 newborns globally. The true incidence in Pakistan is unknown. Data from hospital studies quote an incidence of 1 in 1600–2000. The aim of this study was to uncover existing knowledge of CH and screening for the condition and to assess the impact of health education on mothers' knowledge and attitudes towards having their newborns screened. Methods: The study was conducted from January 2012 to August 2013 at a local hospital in Karachi, Pakistan. This was a prospective, interventional cohort study implemented through a pre- and post-cross-sectional knowledge, attitudes and practices (KAP) survey. Interviews were conducted using structured questionnaires on CH. Results: At baseline (pre-intervention survey), 400 participants consented and 355 (88.9%) completed the study. There was a significant increase in awareness among participating women following the intervention (20% to approximately 98%). Similarly, 78.9% agreed to opt for a screening test for their newborns following delivery as compared with 57.7% in the pre-intervention KAP survey (relative risk 1.38, p-value <0.0001). Conclusion: Unfortunately, the majority of mothers were unaware of CH and its implications, leading to less screening and fewer diagnoses. This study underlines the importance of education in screening programmes to create awareness and maximize uptake.